Isra Mikraj dalam Naskah-Naskah Indonesia - Suryadi, Suryadi (Studia Islamika, 2015)
Th.C. van de Meij and N. Lambooij (eds. & transls.); with the assistance of Oman Fathurrahman, The Malay Hikayat Mi‘rāj Nabi Muhammad: The Prophet Muhammad’s Nocturnal Journey to Heaven and Hell. Leiden - Boston: Brill, 2014, xii +210 pp. (Bibliotheca Indonesica Vol. 37). ISBN 978 90 04 27661 8 (hardback), 978 90 04 27775 5  (e-book).This book provides readers with the Romanization and English translation of an Indonesian manuscript, Cod. Or. 1713, which is held at Leiden University Library in the Netherlands. Written in the eighteenth century and using Jawi script, the text focuses on the Prophet Muhammad’s nocturnal journey to heaven and hell. It is the last leg of the prophet’s two-part miraculous night journey which is well known in the Indonesian and Malay languages as Isra Mikraj Nabi Muhammad. In Indonesia, with the majority of its people embracing Islam, the story – as well as other stories about Muhammad’s life – have been much repeatedly retold by preachers in prayer houses without boredom and enthusiastically listened to with heart by audiences. This story significantly influences Indonesian Muslims’ conception of the ideal living in the world and their perception of the afterlife. Muhammad in his journey rode the heavenly steed of buraq to the seventh stage of the sky (langit ketujuh), where many ordinary Muslims belief hell and heaven are situated. This journey became the focus of the transcribed and translated text, suggesting Nusantara Muslims’ astonishment at this amazing story.DOI: 10.15408/sdi.v22i2.1923